2005
DOI: 10.1002/ijc.21179
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular mapping of uncoupling between vascular permeability and loss of vascular maturation in ovarian carcinoma xenografts: The role of stroma cells in tumor angiogenesis

Abstract: Maintaining homogeneous perfusion in tissues undergoing remodeling and vascular expansion requires tight orchestration of the signals leading to endothelial sprouting and subsequent recruitment of perivascular contractile cells and vascular maturation. This regulation, however, is frequently disrupted in tumors. We previously demonstrated the role of tumor-associated myofibroblasts in vascularization and exit from dormancy of human ovarian carcinoma xenografts in nude mice. The aim of this work was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 38 publications
2
57
0
Order By: Relevance
“…It is well known, however, that both endothelial cells and fibroblasts are located in close association in many epithelial tumors, i.e., in those expressing a desmoplastic response. We recently reported the critical role of myofibroblasts in the initiation of growth of dormant MLS ovarian epithelial tumor xenografts (14), and in the stabilization and maturation of the tumor vasculature (22). These tumor xenografts are not only massively infiltrated by ␣SMA-positive stromal cells (myofibroblasts/pericytes), they are also characterized by a moderate and nonleaky vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known, however, that both endothelial cells and fibroblasts are located in close association in many epithelial tumors, i.e., in those expressing a desmoplastic response. We recently reported the critical role of myofibroblasts in the initiation of growth of dormant MLS ovarian epithelial tumor xenografts (14), and in the stabilization and maturation of the tumor vasculature (22). These tumor xenografts are not only massively infiltrated by ␣SMA-positive stromal cells (myofibroblasts/pericytes), they are also characterized by a moderate and nonleaky vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…This model is of particular interest since in a previous study we reported that the exit of implanted human MLS ovarian carcinoma spheroids from dormancy correlated with the infiltration of ␣-SMA-positive (myo)fibroblasts into the tumor mass, suggesting a critical role for these cells in the initiation of tumor progression (14). Moreover, we recently showed that these stroma myofibroblasts contributed to vascular stabilization and maturation in ovarian tumors by the expression of angiopoietin-1 (22).…”
mentioning
confidence: 98%
“…This is an unsurprising result, based on previous histological studies in tumors that reveal inadequate smooth muscle cells lining the vasculature,3 which would result in an inability to constrict and dilate in response to vasoactive stimuli. The mucinous carcinoma exhibited a notably large response to the gas stimulus relative to surrounding fibroglandular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, heterogeneity of vascular maturation has been demonstrated both between and within tumor subtypes 2. Histological staining of endothelial cells to alpha smooth muscle actin (α‐SMA) can assess vascular maturation,3 but this requires a biopsy, which is invasive, unsuitable for longitudinal measurements, and prone to sampling error. Noninvasive methods that probe vascular function would have potential for characterizing individual tumors, predicting susceptibility to targeted therapies, and monitoring response.…”
mentioning
confidence: 99%
See 1 more Smart Citation